Metallic glass coating for improved needle tattooing performance in reducing trauma: analysis on porcine and pig skins - Jinn P. Chu (Nature Portfolio, 2020)
Abstract The dissemination of tattooing into mainstream culture has raised concerns pertaining to the medical implications of these practices. This paper reports on the coating of tattoo needles with metallic-glass (MG) to reduce trauma to the skin. Extensive experimentation using pork samples and live pigs demonstrated the beneficial effects of non-stick MG coatings. Following 30 insertions into pork skin, significantly less tissue adhered to the MG-coated needles than to uncoated needles. MG-coated needles were also shown to reduce the spread of pigment to the surface of surrounding skin by up to 57%. This resulted in narrower tattoo lines of higher density, indicating that MG-coated needles could be useful in high-resolution tattooing. Histopathological analysis on live pigs revealed severe trauma induced by bare needles, as indicated by the secretion of fluids immediately after tattooing. The wounds formed by coated needles closed within 2 h after tattooing; however, those formed by bare needles remained open for at least 2 h and inflammation was still observed after 3 days. At 5 days after tattooing, skin punctured by the coated needle was entirely healed, whereas skin punctured by the bare needle was still covered with scabs. In addition to the medical benefits, it appears that MG-coated needles could improve the quality of tattoos, based on the fact that the amount of pigment retained in the skin is inversely proportional to the trauma caused by needles.